Severe Preeclampsia in the Setting of Myasthenia Gravis - Adam J. Lake; Antoun Al Khabbaz; Renée Keeney (Case Reports in Obstetrics and Gynecology)
Myasthenia gravis (MG) is a rare autoimmune disease that leads to progressive muscle weakness and is common during female reproductive years. The myasthenic mother and her newborn must be observed carefully, as complications during all stages of pregnancy and the puerperium may arise suddenly. Preeclampsia is a common obstetrical condition for which magnesium sulfate is used for seizure prophylaxis. However, magnesium sulfate is strongly contraindicated in MG as it impairs already slowed nerve-muscle connections. Similarly, many first-line antihypertensive medications, including calcium channels blockers and β-blockers, may lead to MG exacerbation. This case describes the effective obstetrical management of a patient with MG who developed severe preeclampsia. The effective use of levetiracetam and various antihypertensive medications including intravenous labetalol is described. A review of the ten reported cases of MG complicated by preeclampsia is examined to aggregate observations of clinical care, with focus on delivery methods, anticonvulsants, and antihypertensive medications.